EVALUASI PENERAPAN SISTEM INFORMASI PENDAFTARAN ONLINE DI RUMAH SAKIT KUMALA SIWI KUDUS DENGAN HOT-FIT MODEL - Ega Nugraha; Anindya K. W. (Journal of Informatics and Computing, 2023)
The hospital as one of the individual health service facilities is part of the health resources that are very much needed to support the implementation of health efforts. Hospital information systems can encourage increased efficiency and effectiveness of services in hospitals. The process of planning an information system in a hospital is one of the important points that must be prepared. The Kumala Siwi Kudus Hospital has started implementing online registration, but in its planning the Kumala Siwi Kudus Hospital is still in a hurry so that the implementation experiences several obstacles. When viewed from the benefits generated from the system, it is necessary to evaluate the success of its implementation using an information system evaluation model, one of which is the Human Organization Technology-FIT (HOT-FIT). Primary data collection was carried out by interviews and the results of questionnaires conducted on research subjects. The data obtained is a description of the situation when the research was carried out (cross sectional). The results of this study indicate that there is a significant influence on the construct of system quality on the construct of system use.